Lack of association between TYK2 and STAT3 genes and Crohn's disease in the Malaysian population - Lian, L.H.; Lau, T.P.; Lee, V.L.; Lee, W.S.; Hilmi, I.; Goh, K.L.; Chua, K.H. (2013)
This study aimed to investigate the potential association of TYK2 and STAT3 genes with the susceptibility to Crohn's disease (CD) among Malaysians. DNA samples were obtained from 80 CD patients and 100 healthy controls. Polymerase chain reaction-restriction fragment length polymorphism methods were employed for genotyping, followed by statistical analysis. In our current study, none of the single nucleotide polymorphisms of either TYK2 or STAT3 was statistically associated with the susceptibility to CD in our local population (P > 0.05). In contrast, there was a statistically significant association between the G/G homozygotes of the STAT3 rs2293152 and the healthy control group (chi(2) = 6.229, P < 0.05). In conclusion, our study does not support the role of the TYK2 and STAT3 genes influencing CD susceptibility.